The chamber - Davis, John; Foley, James (USA: Universal Home Video [production company] ; Kuala Lumpur : Berjaya HVN [distributor], 1998)
Chris O'Donnell, two-time Academy Award winner, Gene Hackman and Oscar winner Faye Dunaway star in this gripping suspense thriller based on John Grisham's explosive bestselling novel
Executive producer, John Grisham ; screenplay, William Goldman, Chris Reese
Cast: Chris O'Donnell, Faye Dunaway, Gene Hackman
Keywords: Death in motion pictures; Suspense in motion pictures